METHOD OF OPTIMIZING THE TEMPERATURE AND HUMIDITY REGIME OF AIR IN SOLAR GREENHOUSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper presents a comprehensive methodology for optimizing the microclimate—specifically the coupled temperature and humidity regime—within solar greenhouses(geliogreenhouses) operating under variable climatic conditions. Solar greenhousesrepresent a sustainable pathway toward energy-efficient agriculture; however, theirperformance is inherently bound to diurnal fluctuations of solar radiation, resulting inextreme overheating during the day and critical chilling at night, alongside excessiverelative humidity (RH) that triggers fungal pathogens. This research develops a unifiedmathematical model and an engineering framework combining Phase Change Material(PCM) thermal energy storage, automated multi-stage ventilation, and localizeddesiccant dehumidification. The microclimate parameters were simulated usingComputational Fluid Dynamics (FD) and validated against experimental data collectedfrom an autonomous solar greenhouse. The results indicate that the proposedoptimization method reduces nocturnal heating energy consumption by 42.5%, limitsdaytime peak temperatures by 6.8°C, and maintains relative humidity within theoptimal 65–75% range for vegetable crops. The findings demonstrate that dynamic,integrated control of latent and sensible heat fluxes can maximize agricultural yieldwhile eliminating reliance on fossil-fuel-based auxiliary heating systems.
Keywords: Solar greenhouse, microclimate optimization, temperature-humidity regime, thermal energy storage, phase change materials, computational fluid dynamics.